International Society of Biomechanics
Homepage der Internationalen Vereinigung für Biomechanik, u.a. mit folgenden Angeboten Biomechanics Bargain Barn Biomechanical data sources Biomechanical software sources Biomch-L - The E-mail discussion group for biomechanics Conference Announcements Literature sources ISB Publications Resume Postings Standardization documents